Abnormal baseline brain activity in drug-naïve patients with Tourette syndrome: a resting-state fMRI study - Cui, Yonghua; Jin, Zhen; Chen, Xu; He, Yong; Liang, Xia; Zheng, Yi (Frontiers in Human Neuroscience, 2014)
Tourette Syndrome (TS) is a childhood-onset chronic disorder characterized by the presence of multiple motor and vocal tics. This study investigated spontaneous low-frequency fluctuations in TS patients during resting-state functional magnetic resonance imaging (fMRI) scans. We obtained resting-state fMRI scans from seventeen drug-naïve TS children and fifteen demographically matched healthy children. We computed the amplitude of low frequency fluctuation (ALFF) and fractional ALFF (fALFF) of resting-state fMRI data to measure spontaneous brain activity, and assessed the between-group differences in ALFF/fALFF and the relationship between ALFF/fALFF and tic severity scores. Our results showed that the children with TS exhibited significantly decreased ALFF in the posterior cingulate gyrus/precuneus and bilateral parietal gyrus. fALFF was decreased in TS children in the anterior cingulated cortex, bilateral middle and superior frontal cortices and superior parietal lobule, and increased in the left putamen and bilateral thalamus. Moreover, we found significantly positive correlations between fALFF and tic severity scores in the right thalamus. Our study provides empirical evidence for abnormal spontaneous neuronal activity in TS patients, which may implicate the underlying neurophysiological mechanism in TS and demonstrate the possibility of applying ALFF/fALFF for clinical TS studies.